Penerapan Modifikasi Permainan Bola Tangan untuk Meningkatkan Motivasi Siswa Kelas XI-8 dalam Pembelajaran PJOK SMAN 1 Gedangan - Moh. Hamdani; Sasminta Christina Yuli Hartati; Supriyanto Supriyanto (Simpati, 2024)
This research aims to motivate students through the application of ball game modifications in PJOK learning. The type of research used is classroom action research (PTK). The time for conducting the research is for 2 cycles, starting from August to September 2024. The subjects in this class action research (PTK) are students in grades IX-8 of SMA Negeri 1 Gedangan with a total of 35 students consisting of 15 boys and 20 girls. The instruments used to obtain data in this class action research are (1) in the form of observation guidelines and questionnaires. The data analysis used in this study is using quantitative descriptive analysis. The results of this study showed that there was an increase in student motivation through the application of ball game modifications was 4% from the first cycle which then increased to 7% in the second cycle. So it can be concluded that the application of handball game modifications is able to increase student motivation in learning PJOK.